Recognizing Emily and Latisha: Inconsistent Effects of Name Stereotypicality on the Other-Race Effect - Stelter, Marleen; Degner, Juliane (Frontiers in Psychology, 2018)
A person’s name may activate social category information, which has been shown to lead to stereotyping and discrimination in various contexts. However, no previous research has investigated the influence of names on more basic processes of person perception. We present a set of seven experimental studies examining the influence of names on face recognition, namely, on the other-race effect (i.e., the relative difficulty to recognize outgroup faces). White-American participants completed online recognition tasks with White ingroup faces and Black or Chinese outgroup faces. Outgroup faces were presented with typical outgroup names versus typical White names; White faces were presented with typical White names versus infrequent names. We expected better recognition of outgroup faces with typical White names compared to outgroup faces with typical outgroup names. Employing an internal meta-analysis, we observe overall evidence of a small but significant effect (dz = 0.11). However, the pattern of results across the seven studies is inconsistent. Given that particularly the high-powered pre-registered studies did not show an effect, we suggest that the effect should be interpreted with caution. We discuss that a small effect may still have important implications for real life as well as for theories of the ORE, emphasizing the importance of future research regarding the influence of name typicality on inter-group face perception.